Is it just the prayer? : Determining and exploring patients' reasons for choosing a faith-based primary health clinic over their local public sector primary health clinic - Porter, James Dudley (Department of Public Health and Family Medicine, 2016)
Background: Person-centred, re-engineered primary health care (PHC) is a national and global priority. Faith-based health care is a significant provider of PHC in Sub- Saharan Africa but there is very limited published data on the reasons for patient choice of faith-based health care, particularly in South Africa. Aim: The objective of this study was to determine and explore the reasons for patients' choice of a faith-based primary care clinic over their local public sector primary care clinic. The secondary objective was to determine to what extent demography influences reasons for patient choice. Setting: The study was conducted at Jubilee Health Centre (JHC) a faith-based primary care clinic attached to Jubilee Community Church in Observatory, Cape Town, South Africa.